CDK9 inhibitors selectively target estrogen receptor-positive breast cancer cells through combined inhibition of MYB and MCL-1 expression - Mitra, Partha (Oncotarget, 2016)
Our previous studies showed that MYB is required for proliferation of, and confers protection against apoptosis on, estrogen receptor-positive (ER(+ve)) breast cancer cells, which are almost invariably also MYB(+ve). We have also shown that MYB expression in ER(+ve) breast cancer cells is regulated at the level of transcriptional elongation and as such, is suppressed by CDK9i. Here we examined the effects of CDK9i on breast cancer cells and the involvement of MYB in these effects. ER(+ve) breast cancer cell lines including MCF-7 were much more sensitive (> 10 times) to killing by CDK9i than ER(−ve)/MYB(−ve) cells. Moreover, surviving cells showed a block at the G2/M phase of the cell cycle. Importantly, ectopic MYB expression conferred resistance to apoptosis induction, cell killing and G2/M accumulation. Expression of relevant MYB target genes including BCL2 and CCNB1 was suppressed by CDK9 inhibition, and this too was reversed by ectopic MYB expression. Nevertheless, inhibition of BCL2 alone either by MYB knockdown or by ABT-199 treatment was insufficient for significant induction of apoptosis. Further studies implied that suppression of MCL-1, a well-documented target of CDK9 inhibition, was additionally required for apoptosis induction, while maximal levels of apoptosis induced by CDK9i are likely to also involve inhibition of BCL2L1 expression. Taken together these data suggest that MYB regulation of BCL2 underlies the heightened sensitivity of ER(+ve) compared to ER(−ve) breast cancer cells to CDK9 inhibition, and that these compounds represent a potential therapeutic for ER(+ve) breast cancers and possibly other MYB-dependent cancers.